DERIVING HARD CARBON MATERIAL FROM BIOWASTE FOR SODIUM ION BATTERY AND ENHANCING THE ELECTROCHEMICAL PERFORMANCE VIA NITROGEN DOPING. - Maratov, Maksat (School of Engineering and Digital Sciences, 2023)
The current positive trend in the growth of electricity consumption is increasingly pushing humanity to develop and improve the method of obtaining energy from renewable energy sources. One of the system energy optimizations is Grid storage technology. But unfortunately, due to the high price of lithium-ion batteries, these technologies are difficult to pay off. Sodium-ion batteries are considered one of the most promising and cheapest alternatives to replace lithium-ion batteries in Grid storage technology. The limiting factor in the development of sodium-ion batteries is the anode, due to the large ionic radius, sodium ions cannot intercalate into graphite. Hard carbon is the favorite for sodium-ion batteries. Until today, the exact mechanism of the reaction of hard carbon and sodium has not yet been deduced. Studying hard carbon, it was found that doping with heteroatoms can improve the structure for the free penetration of sodium ions into the internal structure of the material. In this work, hard carbon was synthesized from biowaste cherries. The effect of doping hard carbon with nitrogen atoms was studied using urea as a precursor. The result showed that carbon doping improved the hard carbon capacity from 206 mAh g-1 to 274 mAh g-1 at 20 mA g-1. Moreover, hard carbon doped with nitrogen showed a superior capacitance of 110 mAh g-1 at a 1 A current rate.
Keywords: type of access: open access; Sodium Ion Battery